YOUMARES 8 - Oceans Across Boundaries: Learning from each other Proceedings of the 2017 conference for YOUng MARine RESearchers in Kiel, Germany (Springer International Publishing, 2018)
This open access book presents the proceedings volume of the YOUMARES 8 conference, which took place in Kiel, Germany, in September 2017, supported by the German Association for Marine Sciences (DGM). The YOUMARES conference series is entirely bottom-up organized by and for YOUng MARine RESearchers. Qualified early career scientists moderated the scientific sessions during the conference and provided literature reviews on aspects of their research field. These reviews and the presenters' conference abstracts are compiled here. Thus, this book discusses highly topical fields of marine research and aims to act as a source of knowledge and inspiration for further reading and research.